Analisis perbandingan pendapatan nelayan berdasarkan jenis alat tangkap nelayan di Desa Masolo Kecamatan Wawonii Tenggara Kabupaten Konawe Kepulauan - Ermawati; Budiyanto; Piliana, Wa Ode; Kamri, Syamsul; Siang, Roslindah Daeng; Risfandi (Universitas Halu Oleo, 2024)
This research aims to assess the income levels of hook-and-line fishermen and deep-sea longline fishermen in Masolo Village, Wawonii Tenggara District, Konawe Kepulauan Regency, and to compare the income between these two types of fishermen. The research was conducted from November to December 2022, the study sampled 15 fishermen from each group, totaling 30 respondents. Data were collected through interviews, observations, questionnaires, and documentation. Data analysis included total cost, revenue, income analysis, and t-tests. Results showed that tuna hook-and-line fishermen primarily catch tuna and skipjack, while longline fishermen catch red snapper and grouper. The average total costs were IDR 764,121.91 per month for hook-and-line fishermen and IDR760,193.58 per month for longline fishermen. Average revenue per fisherman was IDR 880,000 per month. Net income for hook-and-line fishermen was IDR 11,715,878 per month, while for longline fishermen it was IDR 8,119,806 per month. The t-test analysis using SPSS indicated a significance value of 0.838, which is greater than 0.05, suggesting no significant difference in income between the two groups. Thus, although there is a nominal difference in income, the t-test results show no significant difference.